Comparative study on steel and concrete composite space structures - Lakshmikandhan, K.N.; Senthil, R.; Jayachandran, S.Arul; Sivakumar, P.; Ravichandran, R. (Journal of Structural Engineering, 2025)
The space structures are popular and well accepted in the steel construction industry for many structural applications and also compete successfully with conventional structures. The space structures offer an effective solution to cover large open areas with or without any intermediate supports. Earlier research on space structures has identified the tendency to collapse in a catastrophic brittle manner, caused by the successive buckling of a series of critical compression members. The present study deals with an attempt to alter the brittle characteristics of truss top chord members by introducing concrete slab, which acts compositely with the truss. The truss top chord members and concrete slab are interconnected with shear connectors, which improve the behaviour of the compression members and the overall space truss behaviour. An analytical study based on the finite element method is carried out on composite and noncomposite space frames and the details of the study are presented in the paper. Further the results obtained from the grouping of the truss members are compared with the results obtained from the truss optimization.